Inflection – semantics interfaces in a typological setting: number and non-specific nominal items in Old Spanish legal codices - Nkollo, Mikołaj; Tkaczyk, Magdalena (Lingua Posnaniensis, 2015)
The present inquiry has been spurred by the observation of the morphological behaviour of humandenoting common nouns in Old Spanish codices (13th to 15th century). In spite of the fact that legal norms are designed to apply to an unrestricted number of potential addressees, this class of nominal items surfaces nearly exclusively in the singular, with plural forms being strongly underrepresented. A series of parameters converge to account for this form – function mismatch, thus revealing an essentially interdependent nature of linguistic mechanisms underlying it: type of inflection (inherent vs. contextual), text genre characteristics (distance pole vs proximate pole) and syntactic environment (conditional protases). The pervasiveness of the singular is traced back to non-specificity. Out of two mutually exclusive typological clines accounting for the likelihood of inflectional variation in noun morphology, Definiteness Hierarchy is given preference over degrees of animacy: non-specifically used items, even if highly ranked on animacy scale, are the least likely to surface as plural forms. Competing motivations are assumed to provide a suitable analytical framework to account for typological conflicts such as the one exemplified in Old Spanish legal codices.